Wheeled mobile robotics from fundamentals towards autonomous systems - Klančar, Gregor; Zdešar, Andrej; Blažič, Sašo; Škrjanc, Igor (Butterworth-Heinemann, 2017)
"Wheeled Mobile Robotics covers all the essential knowledge and algorithms that are required in order to achieve autonomous capabilities of wheeled mobile robots. It includes topics from mathematical modeling of motion, sensors and measurements, control algorithms, path planning, probabilistic sensor data fusion. and localization using state estimation filters. The theory is supported with examples that have solutions and excerpts of Matlab code listings in order to make it simple for the reader to try, evaluate, and modify the algorithms. Furthermore, at the end of the book, some interesting practical projects are depicted, which can serve for laboratory practice or to consolidate the theory learned."
Includes bibliographical references and index
Keywords: TECHNOLOGY & ENGINEERING / Engineering (General); Mobile robots; Robotics / Mathematics; Robotics -- Mathematics; Mobiler Roboter